Uji Aktivitas Sel Kanker Payudara T47D Ekstrak Etil Asetat Daun Glodokan Tiang (Polyalthia longifolia L.) Secara In Vitro - Shofi, Muh.; Munawaroh, Siti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Cancer is one of the main causes of death throughout the world. Breast cancer is a non-communicable disease and a type of cancer that is often suffered by women. Breast cancer is a reproductive health problem, both in the world and in Indonesia, which is now a serious concern. Medical treatment of cancer is usually carried out with chemotherapy, surgery and radiotherapy, but the Indonesian people are familiar with and use efficacious plants as an effort to cure various diseases, including cancer. One of them is by using glodokan mast leaves or Polyalthia longifolia L. as natural chemotherapy from biological ingredients. This plant is reported to be high in antioxidant content, so it can be used as an anticancer agent, especially T47D breast cancer. The aim of this research is to examine the compound content and activity of T47D breast cancer cells from P. longifolia leaf extract. This research is basic experimental research, namely by comparing the IC50 value of ethyl acetate extract on young and old leaves. Based on the research results, it is known that the ethyl acetate extract in young and old leaves contains alkaloids, flavonoids, tannins and terpenoids which are useful as anticancer compounds. Cytotoxic activity of ethyl acetate extract of P. longifolia leaves against T47D breast cancer cells with an IC50 value of 253.76 μg/mL on old leaves and young leaves of 220.54 μg/mL with moderate cytotoxicity.